RELAXATION WITH GUIDED IMAGERY AND DEPRESSION IN PATIENTS WITH CANCER UNDERGOING CHEMOTHERAPY - Adriana Cristina Nicolussi; Namie Okino Sawada; Fernanda Mara Coelho Cardozo; Juliana Maria de Paula (Universidade Federal do Paraná, 2016)
The present study aimed to assess the effect of relaxation and guided imagery on depression in cancer patients undergoing chemotherapy. Quasi-experimental study conducted in two chemotherapy centers between 2009-2011. The intervention group was subjected to relaxation with guided imagery; the intervention (n = 73) and control (n = 9) groups completed the Beck Depression Inventory. The most frequent cancers were breast, intestinal and gastric cancers. Statistically significant differences (p <0.05) were observed between the groups (Mann-Whitney test, p = 0.0158) and times (Wilcoxon test, p = 0.0401), and the intervention group had more patients "without depression" than the control group. According to Beck Depression Inventory, the results showed that intervention contributed to reduce the presence of depression among these patients. It is expected that this intervention be disseminated in routine nursing care, so that in the near future cancer patients may benefit from these therapies.